Occupational Exposure and Work-Related Factors Associated with Metabolic Syndrome among Vegetable Farmers - bibit nasrokhatun diniah; Sulistiyani Sulistiyani; Tri Joko; Budiyono Budiyono (The Indonesian Journal of Occupational Safety and Health, 2026)
Introduction: Long-term pesticide exposure can harm farmers. Metabolic syndrome (MetS) occurs due to metabolic disorders associated with the use of pesticides which act as diabetogenic and obesogenic agents. High pesticide use and diverse agricultural activities contribute to the increased incidence of MetS. This study aims to examine the associations between history of direct exposure (HDE) and history of indirect exposure (HIE) to pesticide and MetS, as well as to identify factors associated with MetS among farmers. Methods: This case-control study included 44 cases and 90 controls from 307 male vegetable farmers in Kuningan, Indonesia. Laboratory tests were used for the diagnosis of MetS and pesticide exposure history, which was measured using a questionnaire (coefficients = 0.30 to 0.60; p < 0.05; Cronbach's alpha = 0.718). Data analysis employed binary logistic regression, controlling for age and family history of metabolic disease by examining the Adjusted Odds Ratio (AOR) with a 95% confidence interval (CI). Results: HIE, defined as eating or drinking after spraying, was associated with the occurrence of MetS (p = 0.017; AOR = 3.677; CI: 1.262–10.710). HDE, characterized by watering activities, also showed a significant association (p = 0.010; AOR = 3.012; CI: 1.301–6.974). In total exposure analysis, both factors remained significant (respectively, p = 0.043; AOR = 3.282; CI: 1.041–10.349, and p = 0.043; AOR = 2.430; CI: 1.027–5.747). Conclusion: Frequent watering and the habitual consumption of food and/or beverages after spraying increase the likelihood of developing MetS. Both HIE and HDE significantly contribute to the onset of MetS.